Planificación estratégica en la gestión administrativa de la secretaría de obras públicas-GPAO, para optimizar la operatividad del equipo caminero. - Aguilar Toro, Jorge Iván (2017)
In Latin America, the processes to develop management models are constantly evolving. CORRALES (2006) The concept of model has several associations and connotations. The first and most important is that the word model is associated with the concept of system (p. 5). In Ecuador we are already immersed and penetrated in these models defined in many areas and is taken over by SENPLADES as a product of the management of this unit have been built the national development plans 2009-2013 and 20132017, which counted in its construction process with A massive participation of the citizens of Ecuador. Following the approval of the National Development Plan, called the National Plan for Good Living 2009-2013, SENPLADES and the Decentralized Autonomous Governments generated planning and territorial planning guidelines to consolidate the Decentralized National Participatory Planning System. The Secretariat has participated in the management and updating of the Zonal Development and Territorial Planning Agendas, corresponding to the nine planning zones of the country. These interventions consolidate the articulated construction of a national project from all levels of Government. SENPLADES has worked actively so that the National Plan for Good Living is known by all citizens, without any exclusion. For this purpose, the plan has been published in the Kichwa and Shuar languages ​​as well as in English and was also transcribed to the Braille system. The contribution of this research lies in the support to the administration and management of the Autonomous Provincial Government of El Oro , Is aimed at providing services and public works for the population of the province, through projects that are in tune with their administrative and financial autonomy, allowing strategic planning, developed in the results of this research, synthesizes aspirations Of a continuous improvement in the administration. This research is very important for the institution, since, when carrying out a strategic planning oriented to the administrative management of the Public Works Secretariat to optimize the operation of its road team, it would have adequate management implementing the use of appropriate tools, Which would have a correct control and maintenance; This would optimize the scheduling and compliance of road works; Resulting in an excellent service delivery to the community.